Development of the bank of russia’s fast payment system in modern conditions - S. V. Krivoruchko; I. A. Rizvanova; A. V. Berdyshev (Вестник университета, 2024)
The financial market development in Russia and in the world is currently characterized by a number of processes such as emergence of a large number of new products and new formats implementation for their provision, expansion of the geography of financial institutions presence, national boundaries erasure in acquisition and provision of financial services, sales channels improvement for financial products and services, including remote ones, using modern information technologies. The article studies issues related to the current state and prospects of the fast payment system (hereinafter referred to as FPS) development considering the synergetic impact of payment services digitalization and sanctions restrictions. It analyzes the changes taking place in the FPS service in recent years, focusing on innovative business models, new functions implementation, technological transformations, as well as regulatory and risk aspects. The study pays special attention to the financial technology impact on development and functioning of the system as a key element of the payment industry. The potential of FPS in the context of ensuring the Russian payment infrastructure security represents an important direction for strengthening user confidence and system sustainability. The paper considers a number of promising areas for further development of FPSs, including their applicability to cross-border payments.